Commerce and Conflict: New Data about the Great War. Issue 3 (7th July 2015) - Gowa, Joanne; Hicks, Raymond
Abstract : The First World War is often cited as proof par excellence of the flaws in the liberal peace argument because the adversaries it engaged had been each other's major pre-war trading partners. Although commonly assumed to have wreaked havoc on the trade of the states it engaged, the war's impact on commerce has rarely been rigorously examined. Using an original dataset, this study shows that the Great War triggered substitution processes that reduced its trade-related costs. Although recourse to second-best alternatives always induces efficiency losses, the costs of adjustment were small relative to the other costs that states incurred during the war. The analysis shows that the Great War is not the egregious exception to the theory that conventional wisdom has long assumed it to be. At the same time, it makes clear that the deterrent power of trade varies inversely with belligerents' ability to access the markets of alternative trading partners.